(untitled) (Health and Biosciences, 2026)
Tattooing is increasingly popular among youth and young adults, including university students. While tattoos are often pursued for aesthetic or personal reasons, they pose significant health risks—both infectious and non-infectious—especially when obtained from unregulated sources. This study assessed the awareness, attitudes, and practices related to tattoo-associated health risks among students of Ambrose Alli University, Ekpoma. A descriptive cross-sectional study was conducted among 200 students using a structured questionnaire covering demographics, knowledge of health risks, and tattooing practices. Ethical approval was obtained, and data were analyzed using descriptive statistics. Of the 200 participants, 101 valid responses were analyzed. The average age was 22.15 ± 3.4 years, with females constituting 65.3% of the sample. A high percentage (77.2%) recognized that tattoos could pose health risks. Awareness of infectious complications like HIV and hepatitis was high (83.2%), but fewer respondents (64.4%) were aware of non-infectious risks such as scarring and allergic reactions. While 82.2% had tattoos, only 30.7% signed informed consent before the procedure. Notably, 22.8% reported complications following tattooing. Despite good awareness of infectious tattoo-related risks, knowledge of non-infectious complications and safe practices remains suboptimal among university students. There is a pressing need for educational interventions and stricter health regulations concerning body art practices within and around academic environments.